2012
DOI: 10.1016/j.cell.2012.02.065
|View full text |Cite|
|
Sign up to set email alerts
|

The Skp2-SCF E3 Ligase Regulates Akt Ubiquitination, Glycolysis, Herceptin Sensitivity, and Tumorigenesis

Abstract: Akt kinase plays a central role in cell growth, metabolism and tumorigenesis. Although TRAF6 E3 ligase orchestrates IGF-1-mediated Akt ubiquitination and activation, it is unclear whether TRAF6 is involved in Akt activation by other growth factor receptors as well. Here we show that Akt ubiquitination is also induced by activation of ErbB receptors; unexpectedly, Skp2 SCF complex, but not TRAF6, is a critical E3 ligase for ErbB receptor-mediated Akt ubiquitination and membrane recruitment. Interestingly, Skp2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
267
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 341 publications
(276 citation statements)
references
References 45 publications
8
267
1
Order By: Relevance
“…[4][5][6] As well as the critical role in cell-cycle progression, Skp2 also displays oncogenic activity. 4,5,7 Furthermore, our recent study revealed that Skp2 also played an important role in DNA Damage response (DDR) by regulating ATM kinase and Homologous Recombination (HR) repair. 8 As the 2 main monitoring machineries, lots of evidence indicates that there exists crosstalk between mitosis regulation and DNA repair machinery.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] As well as the critical role in cell-cycle progression, Skp2 also displays oncogenic activity. 4,5,7 Furthermore, our recent study revealed that Skp2 also played an important role in DNA Damage response (DDR) by regulating ATM kinase and Homologous Recombination (HR) repair. 8 As the 2 main monitoring machineries, lots of evidence indicates that there exists crosstalk between mitosis regulation and DNA repair machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that pS477/T479 happens after Akt membrane recruitment, and simply increases the binding affinity between Akt and PDK1, similar to its effect on pS473 and mTORC2. Finally, ubiquitination of Akt on the PH domain by E3 ligases upon growth factor stimulations translocates Akt to the plasma membrane for activation and downstream biological functions such as glycolysis and tumorigenesis [7,8]. It will also be interesting to see the crosstalk between these two important Akt modification events.…”
mentioning
confidence: 99%
“…This study also indicated that ubiquitination‐mediated AKT membrane recruitment does not result from PIP3 binding 80. Apart from this, K14 residue within the PIP3‐binding domain of AKT is required for its with PIP3, which is evident from the inability of binding of mutant (K14R) AKT with PIP3 77, 81, 82. The expression of TRAF2, an E3 ligase, is up‐regulated in the failing heart and its overexpression enhances cardiac hypertrophy and ventricular dysfunction by activating AKT/GSK3β signalling 83…”
Section: K63 Linked Ubiquitination In Akt Activationmentioning
confidence: 63%